(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This scientific article presents about natural and synthetic fabrics, comparative analysis and areas of use, chemical salts of natural and synthetic fabrics, structural properties, and their areas of use in different areas. The article analyzes the differences between natural fabrics and synthetic fabrics and their interaction.